Geospatial Dynamics of The Tasikmalaya-Pangandaran Road Via Singkup its Relationship With Socio-Economics of the Bojongkondang Village Community - Rahma Anugrah, Tega; Siti Fadjarajani; Iman Hilman; Insan Wastuwidya Mahardiani; Koni Dwi Prasetya (International Journal of Geography, Social, and Multicultural Education, 2024)
This research is based on the dynamics of the condition of the Tasikmalaya-Pangandaran road via Singkup, especially the quality of the road which is increasingly decreasing seen from pre-road dynamics to post-road dynamics. The dynamics of road conditions have an impact on other aspects, especially on aspects in society, especially social and economic aspects, especially in terms of work, experiencing social mobility and in terms of income, resulting in conditions of increase and decrease. The aim of the research is to identify the geospatial dynamics of roads and analyze their relationship to the socio-economic conditions of the community. The research method uses a descriptive qualitative approach, the analysis technique uses an income theory formula with the results of income curve modeling. The results of the research show that there are geospatial dynamics on the Tasikmalaya-Pangandaran road via Singkup at 5 points, namely the cule incline block, the nutmeg plantation block, the Kopeng 1 incline block, the Kopeng 2 incline block, and the flat portal block which is characterized by changes in width, depth and length and classification of damage. Analysis of the relationship between the geospatial dynamics of roads and the social conditions of society shows that there is social mobility in society with horizontal, vertical upward, vertical downward and permanent lateral types. Analysis of the economic conditions of the community shows that there is a decline in income, especially from the pre-road dynamics period to the post-road dynamics period, a decline of -12.50% to -60.00%.